Efektivitas LKPD Hidrolisis Garam Berbasis Guided Discovery Learning Terintegrasi Etnosains terhadap Hasil Belajar Murid Fase F SMA - Rhiva Cahya Putri; Andromeda Andromeda (Lembaga Yasin AlSys, 2026)
Students’ learning outcomes in salt hydrolysis material remain relatively low because learning has not fully linked chemistry concepts to real life and local culture, while the effectiveness of ethnoscience-integrated Guided Discovery Learning (GDL)-based Salt Hydrolysis LKPD on students’ learning outcomes has not yet been tested. This study aims to analyze the effectiveness of ethnoscience-integrated GDL-based Salt Hydrolysis LKPD on the learning outcomes of Phase F senior high school students. This study used a quantitative approach with a quasi-experimental method and a pretest-posttest non-equivalent design. The research sample consisted of two classes selected through purposive sampling, namely the experimental class XI F8, which used ethnoscience-integrated GDL-based LKPD, and the control class XI F6, which used the school’s LKPD. Data were collected through pre-tests and post-tests using 20 salt hydrolysis questions and were then analyzed using the N-gain test, normality test, homogeneity test, and hypothesis testing with the assistance of SPSS. The results show that the average N-gain score of the experimental class was 0.77, categorized as high, while that of the control class was 0.64, categorized as moderate. The hypothesis test results obtained a significance value of 0.003 (< 0.05), so H₀ was rejected and H₁ was accepted. The conclusion of this study emphasizes that ethnoscience-integrated GDL-based Salt Hydrolysis LKPD is more effective in improving students’ learning outcomes than the LKPD used at school. These findings contribute to the development of chemistry teaching materials that integrate guided discovery models and ethnoscience contexts and provide practical implications for teachers in designing more contextual and meaningful chemistry learning.